Jacobsen syndrome: Advances in our knowledge of phenotype and genotype. (18th August 2015) - Favier, Remi; Akshoomoff, Natacha; Mattson, Sarah; Grossfeld, Paul; Cody, Jannine DeMars; Battaglia, Agatino; Hale, Daniel Esten
<x xml:space="preserve">Abstract</x> In 1973, the Danish geneticist Petrea Jacobsen described a three‐generation family in which the proband carried a presumed terminal deletion at the end of the long arm of chromosome 11 (11q). This patient had dysmorphic features, congenital heart disease, and intellectual disability. Since Dr. Jacobsen's initial report, over 200 patients with Jacobsen syndrome have been reported, suggesting that Jacobsen syndrome is a contiguous gene disorder. With the advent of high resolution deletion mapping and the completion of the human genome sequencing project, a comprehensive genotype/phenotype analysis for Jacobsen syndrome became possible. In this article, we review research describing individual causal genes in distal 11q that contribute to the overall Jacobsen syndrome clinical phenotype. Through a combination of human genetics and the use of genetically engineered animal models, causal genes have been identified for the clinical problems in JS that historically have caused the greatest morbidity and mortality: congenital heart disease, the Paris–Trousseau bleeding disorder, intellectual disability, autism, and immunodeficiency. Insights gained from these studies are being applied for future drug development and clinical trials, as well as for a potential strategy for the prevention of certain forms of congenital heart disease. The results of these studies will likely not only improve the prognostic and therapeutic approaches for patients with Jacobsen syndrome, but also for the general population afflicted with these problems. © 2015 Wiley Periodicals, Inc.